NEWER ASPECTS IN THE AGE-DEPENDING ALTERATION OF HORSE TEETHING - A. GÁSPÁRDY; ZSÓFIA SIMONYI; F. ESZES; I. BODÓ (Scientific Papers Animal Science and Biotechnologies, 2023)
The authors give a short orientation about the age related parameters of incisors based on the literature. They tell about their own investigation of two conventional (cup depth and its yearly abrasion) and of two first applied (relative abrasion and area of dental table) parameters. The previous literature evaluated the parameters in question in two different ways: time period or frequency analysis. The authors introduced a new method: the linearly-corrected row data which is processed by analysis of variance. Their elaboration reaches altogether 107 individuals, three horse types (English Thoroughbred, English Half-breed and pony), and two genders (mare, stallion + gelding). The cup depth at the levelling is the shallowest in the ponies (2 mm), while it is deeper in the Half-breeds (5 mm) and in the Thoroughbreds (4.4 mm). This deviation can be explained by body size differences between breeds. The degree of the absolute and the relative abrasion of the cup can be associated with the early utilisation (racing) and with the intensive feeding (concentrate). The area of the dental table is the largest in the pony, and the smallest in the Thoroughbred. The reason for the slowest abrasion observed in the ponies can be explained not only by the more traditional feeding but also by the bigger occlusive surface. The authors assume that the selection for the early utilisation of the English Thoroughbred resulted in an automatic change of the well inherited chronology of dentition; more early matured animals producing, in relation to the chronology of dentition. In this breed the general refinement of the whole organism, but especially of the bone system manifests in the narrowing of the teeth also.